Como se estabelece a aliança terapêutica em situações de psicoterapia obrigatória? - Oliveira, Natacha Hennemann de (Universidade do Vale do Rio dos Sinos, 2013)
This dissertation addresses itself to the knowledge, improvement and implementation of issues related to the bond that is established between patient and therapist during psychotherapy, called the therapeutic alliance (TA). The work is organized in two papers, one theoretical and one empirical. The theoretical paper addresses the knowledge of the historical origin of the concept of the therapeutic alliance, from its origins in psychoanalysis until its current conception of atheoretical construct. Based on this concept, the therapeutic alliance (TA) is presented as an essential construct for both the progress of psychotherapy as to obtain positive results. In addition, a number of factors are discussed that can help or hinder the establishment of the alliance, such as characteristics of the patient and the therapist. Thus, the paper shows that if these factors are not observed, TA ruptures may occur. These ruptures may manifest by detachment or by patient confrontation, and it is responsibility of the therapist to identify the ruptures and work with them to prevent early abandonment. The second paper seeks an empirical manner of understanding how TA is established in a specific context that is the mandatory psychotherapy. To this end, 51 patients divided into two groups have been evaluated: mandatory psychotherapy (N = 15) and psychotherapy sought voluntarily (N = 36). Patients in both groups were in psychotherapy at the same institution, and before beginning psychotherapy, they were evaluated in relation to defensive mechanisms (DSQ-40), the object representations (BORRTI - O) and the level of severity of symptoms (SCL-90-R). After the fifth session, the patients were again assessed for TA (CALPAS-p) and coercion perception (through a questionnaire based on the MacArthur Admission Scale-AES-15). The results show that although the mandatory group presents more severe symptoms, and a greater number of individuals have felt compelled to join psychotherapy rather than the original mandatory group, there were no significant differences between mandatory and non-mandatory groups in relation to the TA. Thus, it has been found that it is possible to establish the TA, even in the context of mandatory psychotherapy.
Keywords: Aliança terapêutica; Rupturas da aliança; Psicoterapia obrigatória; Therapeutic alliance; Alliance ruptures; Mandatory psychotherapy; ACCNPQ::Ciências Humanas::Psicologia